Analysis of coordinated grasping kinematics and optimization of grasping force of a parallel hybrid hand. (29th June 2017) - Lu, Yi; Zhang, Canguo; Cao, Chengjun; Liu, Yang
It is important to obtain optimal grasping performance of a parallel hybrid hand in order to reduce the grasping impact force and power loss, to avoid the damage of object or human body during grasping operation or rescue missions. In this article, the coordinated grasping kinematics of the multi-fingers and the optimization of grasping force for a parallel hybrid hand are studied and analyzed systematically. First, the coordinated grasping condition is analyzed, and the formulae are derived for solving the displacement, the velocity, and the acceleration of the contact points between the object and the multi-fingertips of the parallel hybrid hand. Second, the formulae are derived for solving the contact forces at the contact points. Third, the frictional constraints between the multi-fingers and the object are analyzed during stable grasping, and the formulae are derived for solving the optimum contact forces. Finally, an analytic numerical example is given, the analytic solutions of the coordinated grasping kinematics and optimum contact forces are solved and verified by simulation solutions.